Experimental and numerical study on the microstructure and chloride ion transport behavior of concrete-to-concrete interface. (27th February 2023) - Xia, Jin; Chen, Keyu; Hu, Shuting; Chen, Jiejing; Wu, Renjie; Jin, Weiliang
Highlights: The microstructures of new-to-old concrete interfaces, matrix, and ITZ around aggregate were compared via FESEM. Diffusion law of chloride ion in interfaces with various artificial roughness under immersion was analyzed. Good correlations between EPMA/EDS data and traditional method. Chloride migration in interfaces was combined with numerical simulation technology. Abstract: Concrete-to-concrete interfaces present both in new and existing construction, are commonly regarded as the weak link. Durability research of interfaces is a vital prerequisite for structural rehabilitation and strengthening applications under marine and coastal environments. Hence, to clarify the chloride ion transport behavior between the new-old concrete composite system and its constituents, microstructural characteristics of the interfaces with various preparation methods were determined via field emission scanning electron microscopy. Then, the time-dependent diffusion chloride ion penetration together with its steady-state concentration distribution evaluated by using AgNO3 chromogenic, electron microprobe, and energy spectrum methods, as well as the numerical simulation based on the real interface roughness from the 3D laser scanning optical system. Results show that microcracks and a large amount of CaCO3 precipitations were formed in the concrete-to-concrete interface, where its porosity was higher compared to that of the matrix and interface transition zone around coarse aggregate; Therefore, the interface regions have higher tortuosity of water transport channel and strengthen the solution absorption rate, resulting in the internal chloride ions not only diffuse deeper perpendicular to the exposed surface but also ingress into the concrete on both sides as the concentration gradient simultaneously, leading to a "diffusion peak" formation. Furthermore, the effects of groove characteristics (such as orientations, clearance, width, and depth) on chloride transport were modeling evaluated in this study, in which the interfacial relationship could be optimized setting the reasonable groove and achieving the goal of durability equivalent to the cast-in-place structure.